Aggregate and Disaggregate Measures of Operating and Non-Operating Working Capital Influence on Firm Performance: Evidence from Malaysia - Bashir, Rabia; Regupathi, Angappan (UUM Press, 2022)
The study is aimed at investigating the following issues: firstly, whether the different types of working capital, namely operating and non-operating working capital influence the short-term (return on assets) and long-term (Tobin’s Q) firm performance differently, and secondly whether the different measures of operating working capital, namely disaggregated and aggregated (cash conversion cycle) operating working capital, influence the short-term (return on assets) and long-term (Tobin’s Q) firm performance differently. It uses the panel data of 208 listed non-financial firms in Malaysia covering the period from 2013 to 2017, and the data has been sourced from Datastream. It employs the panel corrected standard errors regression model. The study has found that quicker sale of inventory increased both the short-term and long-term performance of the firm. Likewise, faster collection of receivables increased the long-term, but not short- term, performance. However, prompter payment of payables increased both the short-term and long-term performance. The study has also found that the disaggregated working capital measures – inventory, receivables, and payables contributed to a more nuanced influence of working capital on performance, compared to the aggregated working capital. The study has provided novel evidence that– higher non- operating working capital increased firm performance.